Morphological, motor and technical determinants of fighting efficiency of Croatian female cadet age karate athletes - Jukic, J.; Katic, R.; Bala, G. (Collegium Antropologicum, 2013)
The aim of this research was to determine the significance of morphological factors, factors of basic motor and specific motor abilities, and the factors of technical efficiency, on the karate fight success in Croatian female cadet karate athletes. With this purpose, the group of 18 anthropometric measures, 10 basic motor tests, 5 situational karate motor tests, the group of 8 evaluations of 6 basic karate techniques, and 2 karate kata performances was applied on the sample of 101 Croatian karateka aged 14 to 16. Inside the morphological area, the factor analysis isolated: Body mass and volume factor, Subcutaneous fat tissue factor, Longitudinal skeleton dimensionality factor, and Transversal fist dimensionality factor; in the basic motor area: General motor efficiency factor; in the situational motor area: General specific motor efficiency factor; in the area of karate technique performance evaluation: General technical efficiency factor. After that, the application of canonical discriminative analysis determined the differences between high and lower quality karate athletes in the overall area of the isolated factors. The discriminative function showed that high quality female karate athletes compared to those of lower quality differ the most in higher technical efficiency, higher basic and specific motor efficiency, while having somewhat less fat tissue and somewhat wider wrist and fist diameter.